2013
DOI: 10.3928/01913913-20121113-02
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus in Craniosynostosis

Abstract: Strabismus is common in craniosynostosis, with rates from 39% to 90.9% in Crouzon, Apert, Pfeiff er, and Saethre-Chotzen syndromes. This article reviews the epidemiology of strabismus in these disorders and discusses competing theories of the mechanism, including absent muscles, excyclorotation of muscles, and instability of muscle pulleys. The authors then review options for surgical treatment of the often complex ocular misalignment in these disorders. [J Pediatr Ophthalmol Strabismus 2013;50(3):140-148.] PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 62 publications
0
23
1
Order By: Relevance
“…Exotropia is the major type of strabismus in Crouzon syndrome and Apert syndrome. 10 Kreiborg and Cohen 11 reported that the incidence of exotropia in Crouzon syndrome was 76.6% and both the inner and the outer interorbital distances were significantly greater than that of normal orbits, resulting in an increase in the opening angle of the orbits between both lateral walls. Morax 12 studied changes in the position of the eye in patients with Crouzon syndrome after a sagittal expansion of the orbit.…”
Section: Discussionmentioning
confidence: 99%
“…Exotropia is the major type of strabismus in Crouzon syndrome and Apert syndrome. 10 Kreiborg and Cohen 11 reported that the incidence of exotropia in Crouzon syndrome was 76.6% and both the inner and the outer interorbital distances were significantly greater than that of normal orbits, resulting in an increase in the opening angle of the orbits between both lateral walls. Morax 12 studied changes in the position of the eye in patients with Crouzon syndrome after a sagittal expansion of the orbit.…”
Section: Discussionmentioning
confidence: 99%
“…Strabismus complication rates in craniosynostosis have been reported to range from 39% to 90.9%, with the most common type of strabismus in Crouzon and Apert syndromes reported to be exotropia. 15 , 16 Morax reported that the eye position in Crouzon syndrome after sagittal expansion surgery of the orbit changed from preoperative exotropia to postoperative orthophoria in eight of nine patients. 17 …”
Section: Discussionmentioning
confidence: 99%
“…6 Strabismus is also common in patients with UCS, with rates of 39% to 91%. 13,32,56 The primary treatment options for UCS include endoscopic surgery followed by helmet therapy and release operations along with springs or distractors and frontoorbital advancement procedures. Interestingly, early operation seems to increase beneficial outcomes for correction of orbital dysmorphology, ocular abnormalities, and facial asymmetry.…”
Section: Unilateral Coronal Synostosismentioning
confidence: 99%